Injury of neoplastic cells by murine macrophages leads to inhibition of mitochondrial respiration. - Granger, D L (1980)
Cytotoxic activated macrophages (CM) inhibited the growth of neoplastic L1210 cells in vitro but L1210 cell death was minimal to nonexistent. L1210 cells injured by CM were separated from macrophages and studied in an isolated system. CM-injured L1210 cells had an absolute requirement for glucose or another glycolyzable hexose (mannose or fructose) for at least 40 h after removal from macrophages. If the culture medium lacked sufficient concentration of one of these sugars, CM-injured L1210 cells died within 4 h. Uninjured L1210 cells cultured alone or with peptone-stimulated macrophages had no such requirement and maintained complete viability in hexoseless medium. The hexose requirement of CM-injured L1210 cells could not be fulfilled by other naturally occurring monosaccharides, glucose or mannose derivatives, or substrates that can be oxidized by mitochondria. The concentration requirements for glucose, mannose, and fructose by CM-injured L1210 cells correlated with the concentrations required to support maximal glycolysis of these sugars by other murine ascites cells. A concentration of 2-deoxy-D-glucose which completely inhibited L1210 cell glycolysis also complete prevented the ability of glucose or mannose to maintain viability of CM-injured L1210 cells. Interaction with CM led to inhibition of L1210 cell mitochondrial oxidative phosphorylation. This was supported by the findings that: (a) CM-injured L1210 cells had no Pasteur effect; their rate of aerobic glycolysis was the same as the rate of anaerobic glycolysis of uninjured L1210 cells, (b) Endogenous respiration of CM-injured L1210 cells was 15% of normal. Maximal inhibition of uninjured L1210 cell respiration by a specific mitochondrial poison (oligomycin) was nearly the same (13% of normal). It followed that CM-injured L1210 cells required hexose for chemical energy production via the glycolytic pathway. CM-induced mitochondrial injury occurred in five other neoplastic cell lines tested.